Liver transplantation in the mouse: Insights into liver immunobiology, tissue injury, and allograft tolerance. Issue 4 (April 2016) - Yokota, Shinichiro; Yoshida, Osamu; Ono, Yoshihiro; Geller, David A.; Thomson, Angus W.
Abstract : The surgically demanding mouse orthotopic liver transplant model was first described in 1991. It has proved to be a powerful research tool for the investigation of liver biology, tissue injury, the regulation of alloimmunity and tolerance induction, and the pathogenesis of specific liver diseases. Liver transplantation in mice has unique advantages over transplantation of the liver in larger species, such as the rat or pig, because the mouse genome is well characterized and there is much greater availability of both genetically modified animals and research reagents. Liver transplant experiments using various transgenic or gene knockout mice have provided valuable mechanistic insights into the immunobiology and pathobiology of the liver and the regulation of graft rejection and tolerance over the past 25 years. The molecular pathways identified in the regulation of tissue injury and promotion of liver transplant tolerance provide new potential targets for therapeutic intervention to control adverse inflammatory responses/immune‐mediated events in the hepatic environment and systemically. In conclusion, orthotopic liver transplantation in the mouse is a valuable model for gaining improved insights into liver biology, immunopathology, and allograft tolerance that may result in therapeutic innovation in the liver and in the treatment of other diseases.